Assessing and modeling irrigation-induced selenium in the stream-aquifer system of the Lower Arkansas River Valley, Colorado - Herting, Alexander W., author; Gates, Timothy K., author; Colorado State University, publisher (Colorado State University. Libraries, 2006)
Water quality data on dissolved selenium (Se) have been collected since April 2003 in a study area of the irrigated lower Arkansas River Valley, Colorado. Data have been obtained from 22 surface water locations and from 59 ground-water monitoring wells using low-flow sampling techniques. GIS mapping and statistical analysis were used to characterize the occurrence, severity, and spatial-temporal distribution of Se in the study area. Results indicate dissolved Se concentrations ranging from about 0 to 3760 micrograms per liter (μg/l), with a median of 16.6 (μg/l) in the ground water, including three significant "hot spots". River concentrations range from 4.2 to 23.0 μg/l, often exceeding stream standards for aquatic habitat. Relationships are explored between Se concentrations and more-easily-monitored indicators such as electrical conductivity, sulfate concentration, and nitrate concentration. Statistically significant non-linear relationships exist between Se, sulfate, and nitrate con-centration. Uranium (U) concentrations also are found to have a significant relationship with Se. Since high U concentrations have earlier been linked to marine shale and shale-derived soils in the Valley, the relationship between U and Se concentrations suggests a similar linkage between Se and the presence of shale formations. This relationship will be explored further with additional sampling events to test its validity A model of the selenium transport process in the unconfined aquifer, as affected by irrigation practices, is currently being developed and will be calibrated using field data.
Hydrology days 2006
AGU hydrology days 2006
2006 annual AGU hydrology days was held at Colorado State University on March 20 - March 22, 2006.